People Living with HIV Became Influencers on Social Media: Breaking the Stigma - Fitrananda, Charisma Asri; Yusuf, Yogi Muhammad; Rabathy, Qisthy; Bahtiar, Yusuf (JURNAL KOMUNIKASI INDONESIA, 2025)
This study examines the differences in stigma experienced by people living with human immunodeficiency virus (PLHIV) on social media and in broader Indonesian society. When PLHIV disclose their HIV-positive status on social media and attempt to break the stigma by becoming social media influencers, they receive both supportive and critical responses. Negative reactions arise when they are perceived as promoting risky activities, as burdens to the state, or when they face challenges securing sponsorship for their initiatives. This research employs a case study approach to explore the experiences of PLHIV use social media influence as a means to counter HIV-related stigma. Data were collected as part of an HIV-related influencer-centered community. The data were obtained through online observations of the activities of PLHIV influencers on social media and through in-depth interviews with PLHIV influencers. The findings reveal that PLHIV influencers utilize to share knowledge, conduct outreach, and provide consultation about HIV issues to millennials. The result shows that social media platforms help bring personal experiences into the public sphere, shaping public attitudes aligned with the platform characteristics: Twitter serves as an open discussion forum; Instagram functions as a promotional channel for healthy life content; and YouTube podcasts enhance message virality. This research contributes new insights into how HIV stigma is constructed and contested on social media and how influencers act as mediators in creating inclusive, accessible spaces for dialogue. These platforms enable interaction and engagement among professionals, policymakers, PLHIV, and the general public, fostering more participatory health communication ecosystem.